Experimental behavior of transfer story connections for high-rise SRC structures under seismic loading. - Wang, Wei (Earthquake engineering & structural dynamics.)
Results from an investigation aimed at assessing seismic behavior of transfer story connections for high-rise building consisting of steel-reinforced concrete (SRC) frame and reinforced concrete (RC) core tube are presented. Two types of transfer story connections were experimentally evaluated for adequate strength, ductility and energy dissipation. For each type of connection, two large scale subassembly tests were carried out under monotonic and cyclic lateral displacement, respectively. Detailed observations and behavior responses were obtained to contrast the differences between monotonic and cyclic performance of the connections. Test results showed that the SRC column failed before connection collapse and that loading types have little effect on the strength but greatly affect the failure modes and the ductility of the connections. All specimens exhibited good properties of earthquake resistance since they all kept a stable inelastic behavior up to the interstory drift demand suggested by the AISC Seismic Provisions. Based on test observations, support stiffeners with appropriate width-to-thickness ratio and mechanical connectors connecting bars with the steel plate are recommended for design purposes in order to achieve more ductile and reliable seismic behavior of transfer story connections.